The new public management ed. by R.A.W. Rhodes
This special issue draws to gether the results of a research initiative conducted by the Government and Law Committee of the Economic and Social Research Council (ESRC) and tries to provide an analytical picture of developments in Britain in the 1980's. Christopher Hood places British developments in a wider context and reflects upon the significance of British experience. Andrew Dunsire and Keith Hartley test the validity of economic theories of the relationship between organizational status and performance. They explore the proposition that the change from public to private status leads to an improvement in performance. Andrew Gray and Bill Jenkins explore the development of accountable management in ce
Keywords: Public Management; Organization; Management; Public Administration